2022
DOI: 10.1017/s1041610222001028
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness and risk of all-cause, Alzheimer’s, vascular, and frontotemporal dementia: a prospective study of 492,322 individuals over 15 years

Abstract: Objectives: This study examined the association between loneliness and risk of incident all-cause dementia and whether the association extends to specific causes of dementia. Design: Longitudinal. Setting: Community. Participants: Participants were from the UK Biobank (N = 492,322). Intervention: None. Measurements: Loneliness was measured with a standard item. The diagnosis of dementia was derived from health and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…For example, a meta-analysis found that loneliness was associated with a 23% increased risk of dementia. Expanding on the meta-analysis, a UK Biobank study that used the same loneliness measure as the present study found that feeling lonely was associated with an increased risk of Alzheimer disease and vascular and frontotemporal dementia. The current and previous findings suggest that loneliness may be associated with increased risk of neurodegenerative diseases and that the detrimental effects of loneliness are not limited to a single etiologic or neuropathologic pathway.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, a meta-analysis found that loneliness was associated with a 23% increased risk of dementia. Expanding on the meta-analysis, a UK Biobank study that used the same loneliness measure as the present study found that feeling lonely was associated with an increased risk of Alzheimer disease and vascular and frontotemporal dementia. The current and previous findings suggest that loneliness may be associated with increased risk of neurodegenerative diseases and that the detrimental effects of loneliness are not limited to a single etiologic or neuropathologic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Responses were coded as 0 for no and 1 for yes. Pre-vious research 7 has found that this item has a similar association with dementia risk as continuous multi-item scales.…”
Section: Measures and Outcome Ascertainmentmentioning
confidence: 94%
See 2 more Smart Citations
“…Loneliness impacts an estimated 25%–50% of the US population at a given time [ 3 , 5 ], and older adults may be particularly at risk—1 out of 3 individuals over age 45 report feeling lonely, rising to 1 out of 2 individuals over 45 with low income [ 6 ]. Critically, loneliness is recognized as a social determinant of health [ 7 10 ], associated with greater risk for cardiovascular disease [ 11 13 ], dementia and cognitive decline [ 14 23 ], the development and exacerbation of mood disorders including depression [ 2 , 24 29 ], and increases in mortality comparable with smoking [ 26 , 30 33 ]. Eliminating loneliness could prevent an estimated 11%–18% of cases in depression in individuals over 50 [ 2 ].…”
Section: Introductionmentioning
confidence: 99%